Entman Framing Analysis of Food Governance in Online Media - Anggraeni, Diana (Universitas Semarang, 2018)
The article aim is to understand how kompas.com and sindonews.com on the period of 16 October 2017 up to 21 October 2017 framing the news related to food governance in Indonesia using Entman Framing Analysis. Entman Framing is an alternative method to see media differentiation in reveal the reality. According to the researcher, the two media possess its own differentiation in interpreting those realities, so that media could be considered as reader mindset influencer. The concept and theory of the article is agenda setting, reality construct, Entman framing, news and online media. The article method is qualitative using news article as analysis unit. The result show that the two online media emphasize issue about food governance management system. But the assertion of the two news are different; kompas.com tend to build and develop the village and farmer regeneration aspect, while sindonews.com emphasized on reinforcement the management system of food governance.